Knowledge Management: A Case Of "Search And Replace Marketing" Or An Emerging Field Of Management - Ndubisi, Nelson Oly (Asian Academy of Management (AAM), 2004)
This paper critically examines the term "knowledge management" (KM), its components, and the initiatives of a number of organizations that parade as knowledge management pioneers and catalysts, as well as the concept of tacit knowledge. The concept of knowledge management is examined in the web sites of consultancy firms, information practitioners, and other firms that claim to have benefited immensely by implementing knowledge management solutions. In addition a pool of experienced academicians was interviewed to get their views on knowledge management and to furnish information on the knowledge management initiatives in their department/unit etc. The observation made is that the firms are either managing information under the knowledge management nomenclature or managing work practices by instituting an information sharing culture. It is concluded that information management (IM) has been searched and replaced with KM. There is no value added to warrant KM to be an emerging field of management, even the ontology and epistemology of KM at best is ill-defined. In fact KM has no intrinsic meaning